PERSEPSI SISWA TERHADAP PEMBELAJARAN PENJASORKES SAAT PEMBELAJARAN TATAP MUKA DI SMP NEGERI 1 UKUI - Setiawan, M. Imam Agus; Vai, Aref; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2025)
Abstract: The aim of this research is to determine students' perceptions ofphysical education learning during face-to-face learning at SMP Negeri 1 Ukui. Thisresearch was conducted using descriptive research. The method used in this researchuses a survey method. This research was carried out at SMP Negeri 1 UKUI Jl. Poros Lubuk Kembang Bunga Village, Ukui District, Pelalawan Regency. In August-September 2023, face-to-face learning after the Covid-19 pandemic was implemented. The samples from this research were classes VII, VIII and IX. From the mental indicators, the average score was 171.3 with a percentage of 77.9% in the very good category. On the intelligence indicator with an average score of 179.8, the percentage value of 81.7% is in the very good category. Then the physical indicator obtained an average score of 178.5 with a percentage of 81.1% in the very good category. Furthermore, the environmental and parental indicators with an average score of 186.3, a percentage value of 84.7%, are in the very good category. In the infrastructure indicator, the average score was 164.7 with a percentage of 74.8% in the good category. The results of research on students' perceptions of physical education learning during face-to-face learning at SMP Negeri 1 Ukui overall indicators with an average score of 173.1 and the respondent's achievement level was 78.7% in the very good category.Keywords: Perception of Learning, Face to Face